Adaptation to robust monolayer expansion produces human pluripotent stem cells with improved viability - Kunova, Michaela; Matulka, Kamil; Eiselleova, Livia; Salykin, Anton; Kubikova, Iva; Kyrylenko, Sergiy; Hampl, Ales; Dvorak, Petr (Stem cells translational medicine, 2013)
The generation of human pluripotent stem cells (hPSCs) of sufficient quantity and quality remains a major challenge for biomedical application. Here we present an efficient feeder-free, high-density monolayer system in which hPSCs become SSEA-3-high and gradually more viable than their feeder-dependent counterparts without changes attributed to culture adaptation. As a consequence, monolayer hPSCs possess advantages over their counterparts in embryoid body development, teratoma formation, freezing as a single-cell suspension, and colony-forming efficiency. Importantly, this monolayer culture system is reversible, preserving the competence of hPSCs to gradually reacquire features of colony growth, if necessary. Therefore, the monolayer culture system is highly suitable for long-term, large-scale propagation of hPSCs, which is necessary in drug development and pluripotent stem cell-based therapies.
Keywords: viabilita buněk; Cell Line; podkladové buňky; biologické markery; Teratoma; Cell Proliferation; Biomarkers; Pluripotent Stem Cells; buněčné kultury; Cell Survival; teratom; Induced Pluripotent Stem Cells; pluripotentní kmenové buňky; analýza kolonii tvořících jednotek; indukované pluripotentní kmenové buňky; Animals; lidé; Humans; zvířata; Cell Culture Techniques; myši; buněčné linie; proliferace buněk; Feeder Cells; Mice; Colony-Forming Units Assay